UJI EFEKTIVITAS ANTIMIKROBA EKSTRAK DAUN SIRSAK (Annona muricata L.) TERHADAP BAKTERI Aeromonas hydrophila, Edwarsiella tarda DAN FUNGI Saprolegnia sp. - Friyuanita Lubis; Dwi Suryanto; Yunasfi Djayus (AQUACOASTMARINE, 2015)
This study was aimed to determine antimicrobial effectivity of soursop leaf (Annona muricata L.) against bacterial pathogens Aeromonas hydrophila, Edwarsiella tarda and fungus Saprolegnia sp. and to determine the extract toxicity to Artemia salina Leach. Extraction was done by maceration method using methanol, ethyl acetate and n-hexane. Phytochemical test was conducted to all extracts. Antimicrobial effectivity test was done using the agar diffusion method. Toxicity test was conducted using Brine Shrimp Lethality Test. The result of phytochemical test of soursop leaf extract showed that the extract contained of alkaloid, phenolic, and steroid/terpenoid. Antimicrobial test showed that the soursop leaf extract inhibit Aeromonas hydrophila, Edwarsiella tarda bacteria to some extent while fungus Saprolegnia sp. was not inhibited. All extracts were medium and highly toxic. LC50 of extract of ethyl acetate, methanol and n-hexane were 12.16, 13.07, 63.23 ppm, respectively.Keywords: Antimicrobial effectivity, Toxicity, Aeromonas hydrophila, Edwarsiella tarda, Saprolegnia sp.